Awareness and Attributes of Employability Skill amongst Nigerian Graduates of Higher Education and the Enhancement of Initiatives - Benjamin, Johnson; Raju, Valliappan; Mawo, Martin Luther; Chibuzo, Johnson Katherine (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to analyse the awareness and attribute of employability skill amongst Nigerian graduates. Every student of Higher Education is in school studying and expecting to graduate someday, and thereafter secure a job or establish a business. While some students try hard to build up initiatives after graduation, most are down helplessly as they keep searching for job without hope. Global prospects for employment has worsen, including Nigeria which has a population of about 200 million people. Even with the continuous progress made in funding institutions of higher learning and empowering the labour market, Nigerian university graduates have also submitted their dissatisfaction in regards to the high level of unemployment. On this note, what is required of the graduates or graduating students in securing employments? Why do employees seek for 3 to 5 years working experience knowing that fresh graduates does not possess that? Are the students’ taught using newest technologies and equipment that can be seen in the competitive labour market? And how can employees and the universities enhance the student’s talent. With these questions in mind, this paper reviews the findings in other previous literature and relate it to Nigerian graduates. Recently, low academic standard sees the university graduate as unqualified. As a result of this, most graduates find it difficult to secure employment relating to their field of study upon graduation. Therefore, this paper seek to analyse the aspect of the employability awareness thus investigating the employability skill of Nigerian university graduates. Although this study is based on casual interview with few employers of public enterprises, private organisations, some Nigerian graduate and undergraduate students, it explores the development of the ‘employability’ agenda in higher education. It also examines the nature and effect of organisational change for graduates by evaluating what attributes graduates will need in the next decade.